Tom J. Geraghty papers - Geraghty, Tom J.; McLeod, Norman Z., 1898-1964.
Correspondence, scripts, notes, articles, printed matter, cartoons, and photographs relating to Geraghty's career as a journalist, producer, and screenwriter; his personal life; and his friendships with film personalities, including George Ade, Douglas Fairbanks, W.C. Fields, and Mary Pickford. Geraghty's daughter, Sheila Gladys Geraghty has annotated portions of the collection. Includes papers of Norman Z. McLeod. Correspondents include Geraghty's son, Maurice Geraghty, George Ade, W.C. Fields, L. Wolfe Gilbert, Sadakichi Hartmann, Kin Hubbard, Gertrude Lawrence, Mary Pickford, Julian Street, and Booth Tarkington.
In part, typewritten transcripts.
Journalist, motion picture producer, and screenwriter. Also known as Thomas J. Geraghty. Born 1883, died 1945.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ade, George, -- 1866-1944.; Ade, George, -- 1866-1944 -- Correspondence; Fairbanks, Douglas, -- 1883-1939.; Fields, W. C. -- 1880-1946.; Fields, W. C. -- 1880-1946 -- Correspondence; Geraghty, Maurice, -- 1908-1987 -- Correspondence; Geraghty, Sheila Gladys; Gilbert, L. Wolfe -- 1886-1970 -- Correspondence; Hartmann, Sadakichi, -- 1867-1944 -- Correspondence; Hubbard, Kin, -- 1868-1930 -- Correspondence; Lawrence, Gertrude -- Correspondence; Pickford, Mary, -- 1892-1979.; Pickford, Mary, -- 1892-1979 -- Correspondence; Street, Julian, -- 1879-1947 -- Correspondence; Tarkington, Booth, -- 1869-1946 -- Correspondence; Journalism; Motion picture actors and actresses; Motion picture industry; Motion picture plays; Motion pictures -- Production and direction; Journalists; Motion picture producers; Screenwriters